ABOUT CHATBOTS, THEIR RELEVANCE AND IMPORTANCE FOR IT STUDENTS - Bazhan , Stanislav (Collection of scientific papers «ΛΌГOΣ», 2023)
The rapid development of the IT industry in recent years has brought about revolutionary advancements and transformative changes across various sectors of society, impacting how we live, work, and interact with technology. In light of these profound shifts, it becomes increasingly imperative for individuals and organizations to recognize the significance of aligning with these emerging trends and embracing the ever-evolving landscape of the IT field to stay competitive and foster innovation.